Predictors of Health Laboratory Professionals' Practices and Its Relation To Service Interruptions, In Public Hospitals In Saudi Arabia - Ghaida Ghazi Alwithnani; Shuruq Sharaf Alsharif; Abdulaziz Faisal Alamoudi; Khalid Mesfer Safir Alkhathami; Mha Sad Faleh Alatibi; Fatinah Manajaa Alotaibi; Ali Saeed Hamed Alghamdi; Hamzah Hamed Abbad Alsharif; Ahmed Saeed Tuhami; Ibrahim Abdullah Nader Shah; Majed Owaid Abdullah Alsulami (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Quality laboratory services are key in the healthcare system for successful diagnosis and patient care. Uninterrupted laboratory services are needed to meet the needs of all patients and clinical personnel, but studies in developing nations revealed that most clinicians were dissatisfied due to the lack of quality laboratory services and frequent interruptions. Objective: This study aimed to assess the level of health laboratory service quality, service interruptions, and its predictors in public Hospitals in Harar town, eastern Saudia Arabia. Method: A facility-based cross-sectional settings Research design: This study employed a descriptive research approach, a cross-sectional study was carried out utilizing a questionnaire. In order to evaluate the variables influencing the caliber of laboratory services at Saudi Arabia's public healthcare facilities,. 233 nurses was accepted to assigned in the research . Setting: East Jaddah Hospital . it was conducted between January and April 2024. Data collection utilized Standardized Stepwise LaboratoryImprovement Process Towards Accreditation (SLIPTA) checklists andquestionnaires based on the Saudia Arabian Hospital Standard TransformationGuidelines. Data were entered and analyzed by Statistical Package for theSocial Sciences, version 26. Descriptive statistics such as frequencies,proportions, and means, were calculated. Results: 150 (61.5%) of the 300 laboratory professionals that took part in the study held a bachelor's degree. The majority of professionals, 200 (70.0%), did not participate in any training linked to their jobs. 100 (25.0%) respondents thought that their labs did not offer high-quality laboratory services, and the main factors influencing the provision of high-quality services were lack of resources (80%), inadequate management support (70%), low-quality equipment (40%), excessive workload (30%), improper calibration of equipment (25%), and ignorance (15%). Conclusion: In conclusion, insufficient management commitment, inadequate human resource management, inadequate resource provision, inefficient communication, and a lack of a well-established quality management system were the main variables influencing the quality of laboratory services.